Dystonia Linked to EIF4A2 Haploinsufficiency: A Disorder of Protein Translation Dysfunction - Harrer, Philip; Škorvánek, Matej; Kittke, Volker; Dzinovic, Ivana; Borngräber, Friederike; Thomsen, Mirja; Mandel, Vanessa; Svorenova, Tatiana; Ostrozovicova, Miriam; Kulcsarova, Kristina; Berutti, Riccardo; Busch, Hauke; et al. (Movement disorders, 2023)
BACKGROUND: Protein synthesis is a tightly controlled process, involving a host of translation-initiation factors and microRNA-associated repressors. Variants in the translational regulator EIF2AK2 were first linked to neurodevelopmental-delay phenotypes, followed by their implication in dystonia. Recently, de novo variants in EIF4A2, encoding eukaryotic translation initiation factor 4A isoform 2 (eIF4A2), have been described in pediatric cases with developmental delay and intellectual disability. OBJECTIVE: We sought to characterize the role of EIF4A2 variants in dystonic conditions. METHODS: We undertook an unbiased search for likely deleterious variants in mutation-constrained genes among 1100 families studied with dystonia. Independent cohorts were screened for EIF4A2 variants. Western blotting and immunocytochemical studies were performed in patient-derived fibroblasts. RESULTS: We report the discovery of a novel heterozygous EIF4A2 frameshift deletion (c.896_897del) in seven patients from two unrelated families. The disease was characterized by adolescence- to adulthood-onset dystonia with tremor. In patient-derived fibroblasts, eIF4A2 production amounted to only 50% of the normal quantity. Reduction of eIF4A2 was associated with abnormally increased levels of IMP1, a target of Ccr4-Not, the complex that interacts with eIF4A2 to mediate microRNA-dependent translational repression. By complementing the analyses with fibroblasts bearing EIF4A2 biallelic mutations, we established a correlation between IMP1 expression alterations and eIF4A2 functional dosage. Moreover, eIF4A2 and Ccr4-Not displayed significantly diminished colocalization in dystonia patient cells. Review of international databases identified EIF4A2 deletion variants (c.470_472del, c.1144_1145del) in another two dystonia-affected pedigrees. CONCLUSIONS: Our findings demonstrate that EIF4A2 haploinsufficiency underlies a previously unrecognized dominant dystonia-tremor syndrome. The data imply that translational deregulation is more broadly linked to both early neurodevelopmental phenotypes and later-onset dystonic conditions. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: Dystonic Disorders; MicroRNAs; pohybové poruchy; translational dysfunction; Adolescent; Dystonia; mikro RNA; Child; Protein Biosynthesis; proteosyntéza; dítě; haploinsuficience; dystonické poruchy; Peptide Initiation Factors; Movement Disorders; Tremor; mladiství; tremor; dystonie; lidé; EIF4A2; Humans; iniciační faktory; dystonia; Haploinsufficiency; loss-of-function variants